Implementation of Ball Feeling to The Results of Dribbling Agility in Football Games - Muhamad Ghiffari Amrullah Dwipayana; Dewi Susilawati; Respati Mulyanto (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to solve the problem of ball feeling on dribbling agility so that players have good dribbling quality and are right in the direction of the ball's goal. The sample of this study was football students aged 11-12 years in the Sumedang area, namely SSB Bina Putra Pamekar. The number of samples of this study was 16 football training participants, this research test consisted of 1 type, namely the zig-zag ball feeling test where the ball must remain controlled at a distance of feet, the speed test is the same as the zig-zag test with a distance of 5 meters. Lack of dribbling agility in the game of soccer, this ball feeling can have the right influence on dribbling agility in the soccer game. In line with the title of the research that the researchers took, this study uses the Experiment method with the research design using one group pretest-posttest design, because it is to determine the influence and magnitude of the influence of the results of the research taken. The results of research conducted by researchers that the implementation of ball feeling affects dribbling agility in football games, the magnitude of the influence is 0.02.